An Endoplasmic Reticulum/Plasma Membrane Junction: STIM1/Orai1/TRPCs - Lee, Kyu pil (2009)
Ca2+ entering cells through store-operated channels (SOCs) affects most cell functions, and excess SOC is associated with pathologies. The molecular makeup of SOCs and their mechanisms of gating were clarified with the discovery of the Orais and STIM1. Another form of SOCs are the TRPCs. STIM1 gates both Orai and TRPC channels but does so by different mechanisms. Although the STIM1 SOAR domain mediates the binding of STIM1 to both channel types, SOAR is sufficient to open the Orais but the STIM1 polylysine domain mediates opening of the TRPC channels. This short review discusses recent findings on how STIM1 gates and regulates the Orais and TRPCs, and how the STIM1/Orai1/TRPCs complexes may function in vivo to mediate SOC activity.